The replica of human respiration system to improve student's interpretation skill - Rikha Zulia; Siti Alimah (Universitas Negeri Jakarta, 2023)
Visual media are tools used to deliver information to students, especially on material that cannot be sensed directly by humans. One of them is the material of the human respiratory system. The purpose of this study is to analyze the improvment of the replica of human respiration system in improving student’s interpretation skills. This research is an experimental study with a quasy experimental design with a sample size of 78 students. The method of collecting data on interpretation skills uses a multiplechoice test instrument with a total of 20 questions. The data were analyzed quantitatively using the independent sample t-test. The improvment of this study is determined by the following indicators: 1) classical completeness class 50%, 2) N-gain value is in the moderate category, and 3) there is a significant average difference between the control and the experimental class. The results of this study indicate that the classical completeness in the experimental class is higher than the control class. The N-gain value of the experimental class is in the medium category and the control class is in the low category. The results of the average difference test of the two groups showed a significant difference between the average learning outcomes of the experimental class and the control class. Based on these results, it can be concluded that the replica of human respiratory system is improving students' interpretation skills.